Effectiveness of the NIZKP Protocol for Authentication in IoT Environment - Yann Cedric Lawson, Teyi; T, Senthilnathan (International Journal of Engineering and Technology, 2018)
Elliptic Curves when compared to other encryptions scheme such as RSA etc., provides an equivalent security, smaller key sizes, less power consumption, faster calculations, less bandwidth used and is more suitable for Internet of Things devices. In addition of encrypting the data, the devices in the network should also be able to authenticate themselves, which can be achieved with the implementation of â€œNon-Interactive Zero Knowledge protocolâ€ (NIZKP). This protocol involves two parties: The prover and the Verifier. Prover party should prove to the Verifier that they have the knowledge of something, without revealing what is it. In this paper, a study of Schnorr protocol or âˆ‘- protocol over Elliptic Curves is done and the protocol is implemented in Python using the Python Cryptography Toolkit PyCrypto which is a collection of cryptographic modules implementing various algorithms and protocols. Finally, the results were compared with Elliptic Curve Diffie-Hellmann(ECDH) and present a performance evaluation of the protocols on the Raspberry Pi 3B model, a credit-card sized computer used for the development of IoT devices hence the perfect platforms to test the protocol.Â Â